Augmenting customer loyalty through customer experience management in the banking industry - Makudza, Forbes (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to analyse and evaluate the effect of customer experience management (virtual interaction, physical interaction and service interaction) on customer loyalty in the banking industry. Design/methodology/approach The study followed an explanatory research design to sample 384 respondents. Stepwise regression analysis was used to validate the relevance of the study model. Findings The results indicated that there is a positive association between customer experience management and customer loyalty. The dimensions of customer experience management, namely virtual interaction, physical interaction and service interaction, were also found to be statistically significant in explaining customer loyalty behaviour. Practical implications The study practically influences the way banks and other financial institutions gain competitive advantage through managing the experiences of customers in a volatile business environment. At a time when banks are no longer the only providers of financial services, the study offers a road map to reduce portfolio purchasing and switching behaviour through enhanced experience management at all customer touch points. Originality/value The study presents an augmented model of customer experience management which is linked to consumer loyalty.